Radial velocities and axial rotation for a sample of chemically peculiar stars - Levato, Hugo (1996)
As part of a systematic project we have determined radial velocities and projected rotational velocities for a sample of 186 chemically peculiar stars which have been observed by the Hipparcos' satellite. The purpose is to provide necessary data to study the space velocities of peculiar stars.